PENGARUH TEKANAN DAN KECERDASAN EMOSIONAL TERHADAP KUALITAS AUDIT PADA PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BANTEN - Syamsuri Syamsuri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
This study discusses the client’s understanding of intelligence and emotions on audit quality (empirical study on in the South Tangerang area). In this study using a survey method with a questionnaire. The object of this study is the auditors who work in the South Tangerang, Banten Province. The total sample 45 respondents obtained from 5 KAP is KAP Ruslim dan Ruslim, KAP Tri Bowo Yulianti, KAP Noor Salim & Rekan, KAP Heliantono & Rekan dan KAP Kadim, Veronica & Syahirman. The results of the study revealed that the audit quality of financial statements is not always going well, pressure and dictation from the company are one of the reasons for poor audit results. However, emotional intelligence can be a middle ground for these problems.In other words, an auditor's discretion can reduce bad actions,as well as self-protection from the bad influence of the organization. Keywords: Pressure, Emotional Intelligence, Audit Quality